2019
DOI: 10.1097/md.0000000000017645
|View full text |Cite
|
Sign up to set email alerts
|

Increased Elabela levels in the acute ST segment elevation myocardial infarction patients

Abstract: Elabela is a bioactive peptide and a part of Apelinergic system. Elabela has an important role in the early embryonic stages. Elabela's beneficial effects in cardiovascular system were shown in some animal models or in vitro studies. Lately, some investigational studies in humans are started to be seen in literature. Our aims were to investigate serum Elabela levels in the first day of ST segment elevation myocardial infarction (STEMI), to compare with healthy controls, and to see if there is a correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
(24 reference statements)
2
15
0
1
Order By: Relevance
“…Sato et al showed that apela can prevent pressure overload heart failure caused by transverse aortic constriction in mice 27 . Yurdaer et al found that the apela level was positively correlated with NT‐proBNP ( r = 0.586, P < 0.05), whereas the levels of apela (( r = −0.551, P < 0.05) or NT‐proBNP ( r = −0.684, P < 0.05) were negatively correlated with LVEF in patients with acute MI 14 . BNP or NT‐proBNP is an important biomarker to evaluate the severity and prognosis of heart function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sato et al showed that apela can prevent pressure overload heart failure caused by transverse aortic constriction in mice 27 . Yurdaer et al found that the apela level was positively correlated with NT‐proBNP ( r = 0.586, P < 0.05), whereas the levels of apela (( r = −0.551, P < 0.05) or NT‐proBNP ( r = −0.684, P < 0.05) were negatively correlated with LVEF in patients with acute MI 14 . BNP or NT‐proBNP is an important biomarker to evaluate the severity and prognosis of heart function.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently, clinical studies have shown that endogenous plasma apela levels are higher in patients with acute myocardial infarction (MI) than in healthy controls; furthermore, apela levels are also negatively correlated with left ventricular ejection fraction (LVEF). 14 These basic experiments and clinical studies suggest that apela is valuable in the diagnosis and treatment of cardiovascular disease. In this study, we prepared a heart failure model of MI in mice to further investigate the effects of exogenous apela intervention on the heart and kidney function of mice with AMI as well as to explore the possible underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal test, the infusion of ELA im- proved cardiac dysfunction, hypertrophy, and fibrosis. 15,16) In a recent report, Dönmez, et al 9) have found that the ELA levels increased in patients with STEMI. In addition, they observed a moderate positive correlation between troponin I and ELA.…”
Section: Discussionmentioning
confidence: 93%
“…8) However, so far, there is only one clinical data on the association between ELA level and ST elevation myocardial infarction (STEMI). 9) The present study was conducted to clarify the circulating ELA concentrations in patients with CHD and reveal the relationship with CHD and the disease classification.…”
mentioning
confidence: 99%